Echocardiographic Assessment of Embryonic and Fetal Mouse Heart Development: A Focus on Haemodynamics and Morphology - Nathan D. Hahurij; Emmeline E. Calkoen; Monique R. M. Jongbloed; Arno A. W. Roest; Adriana C. Gittenberger-de Groot; Robert E. Poelmann; Marco C. De Ruiter; Conny J. van Munsteren; Paul Steendijk; Nico A. Blom (The Scientific World Journal)
Background. Heart development is a complex process, and abnormal development may result in congenital heart disease (CHD). Currently, studies on animal models mainly focus on cardiac morphology and the availability of hemodynamic data, especially of the right heart half, is limited. Here we aimed to assess the morphological and hemodynamic parameters of normal developing mouse embryos/fetuses by using a high-frequency ultrasound system. Methods. A timed breeding program was initiated with a WT mouse line (Swiss/129Sv background). All recordings were performed transabdominally, in isoflurane sedated pregnant mice, in hearts of sequential developmental stages: 12.5, 14.5, and 17.5 days after conception (n=105). Results. Along development the heart rate increased significantly from 125 ± 9.5 to 219 ± 8.3 beats per minute. Reliable flow measurements could be performed across the developing mitral and tricuspid valves and outflow tract. M-mode measurements could be obtained of all cardiac compartments. An overall increase of cardiac systolic and diastolic function with embryonic/fetal development was observed. Conclusion. High-frequency echocardiography is a promising and useful imaging modality for structural and hemodynamic analysis of embryonic/fetal mouse hearts.